TGF-β3 promotes vascular normalization of prostate cancer to potentiate immunotherapy and chemotherapy - Qiliang Teng; Niu Wang; Hanqi Lei; Tongyu Tong; Yupeng Guan; Mengjun Huang; Fei Cao; Bin Xu; Jia Yang; Yimian Huo; Wenping Chen; Ran Bi; et al. (Cancer Immunology, Immunotherapy)
Abstract Background Prostate cancer (PCa) has previously been established as a cold tumor with highly complex tumor environment. Transforming growth factor (TGF)-β1 plays pro-oncogenic roles in PCa. TGF-β3, another isoform of the TGF-β family, is reported to have different and even opposite regulatory roles to TGF-β1. However, the effect of TGF-β3 in PCa has not been elucidated. Methods TGF-β3 expression and its association with multiple clinicopathological characteristics were analyzed immunohistochemically in human PCa specimens. The antitumor effect of TGF-β3 and its combination with immunochemotherapy was observed by subcutaneous xenograft tumor model. RNA-seq of mouse tumor tissues identified differentially expressed genes (DEGs) that were enriched in vascular biological processes. The angiogenesis effect of TGF-β3 was evaluated using tube formation assay. Hypoxic area, NG2+ pericytes, Col IV+ basement membrane, adhesion molecules and immune cells were analyzed by immunofluorescence. Vascular permeability was measured by Evans blue staining. The flow cytometry was conducted to examine the composition of tumor-infiltrating CD8+ T cells. Results Low TGF-β3 expression in prostate cancer (PCa) was correlated with higher Gleason scores and pathological T stage. While intratumoral TGF-β3 injection demonstrated antitumor effects in vivo, it did not directly affect PCa cell proliferation, migration or invasion in vitro. GO analysis revealed significant enrichment of DEGs in vascular-related biological process. TGF-β3 treatment normalized tumor vascular architecture and reduced vascular leakage. This vascular normalization upregulated endothelial adhesion molecules and enhanced CD8+ T cell infiltration, suppressing tumor growth. Critically, TGF-β3-induced vascular normalization synergized with anti-PD-L1 immunotherapy or paclitaxel chemotherapy, enhancing CD8+ T cell or drug infiltration and significantly boosting therapeutic efficacy. Conclusions TGF-β3 potentially acts as a protective factor in PCa by promoting vascular normalization and remodeling of the tumor environment, which facilitates infiltration of CD8+ T cells or drugs, significantly enhancing their antitumor effects.